Metal cation doped polymetallic sulfide nanosphere as well as preparation method and application thereof

By using metal cation doped polymetallic sulfide nanospheres as catalysts, the existing electrolytic catalysts, precious metal catalysts are solved, and the catalytic activity of non-metallic catalysts are poor, thus achieving efficient electrolytic catalytic effect.

CN119843315APending Publication Date: 2025-04-18HEBEI NORMAL UNIV FOR NATTIES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510031785.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing electrolytic catalysts: precious metal catalysts are expensive and have limited reserves, and non-metallic catalysts have poor catalytic activity, resulting in low catalytic efficiency of electrolytic water.

Method used

Metal cation-doped polymetallic sulfide nanospheres are used as catalysts. The material consists of molybdenum sulfide and doped cobalt sulfide, and is prepared by hydrothermal reaction or solvothermal reaction to form a nanosphere structure to improve catalytic activity.

Benefits of technology

The material exhibits excellent bifunctional catalytic performance of hydrogen evolution and oxygen evolution reaction, significantly improves the catalytic efficiency of electrolyzed water, and is cheap and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843315A_ABST
    Figure CN119843315A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalytic materials, and particularly relates to a metal cation doped polymetallic sulfide nanosphere as well as a preparation method and application thereof. The metal cation doped polymetallic sulfide nanosphere is formed by polymetallic sulfide nanosheets, and polymetallic sulfide comprises molybdenum sulfide and metal cation doped cobalt sulfide; the metal cations comprise nickel ions and / or manganese ions. The material has excellent bifunctional catalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), shows excellent water electrolysis performance, and can effectively improve the catalytic efficiency of water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic materials, and specifically relates to metal cation-doped multimetal sulfide nanospheres and a preparation method and application thereof. Background Art

[0002] As a new type of energy, hydrogen energy is favored by scientists for its clean, pollution-free, green and renewable advantages. It is considered to be an ideal alternative energy source for mankind to fundamentally solve global problems such as energy and environment. In order to solve environmental pollution, water electrolysis has become an important part of modern clean energy technology. Water electrolysis has been widely used due to its mature process, easy operation, and green and pollution-free advantages. The water electrolysis process consists of two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The high overpotential in the HER and OER processes affects the catalytic efficiency of water electrolysis.

[0003] Using water electrolysis catalysts is an effective way to reduce the reaction barrier. Common water electrolysis catalysts include precious metals, transition metals, and non-metallic catalysts. At present, the commercial HER catalyst Pt / C and OER catalyst RuO2 / IrO2 are precious metal catalysts, but their high price and small reserves are not conducive to large-scale industrial electrolysis of water to produce hydrogen, which greatly limits practical applications; and non-metallic catalysts have poor catalytic activity. Therefore, transition metal catalysts that are easy to form complexes, have variable valence states, are cheap, have abundant reserves, high catalytic activity, and good stability have become the main body of research. However, compared with precious metal catalysts, the catalytic activity of transition metals is still poor. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a metal cation doped multi-metal sulfide nanosphere and its preparation method and application, the material has excellent bifunctional catalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), and can effectively improve the catalytic efficiency of water electrolysis.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a metal cation-doped polymetallic sulfide nanosphere, wherein the nanosphere is formed from polymetallic sulfide nanosheets, wherein the polymetallic sulfide in the polymetallic sulfide nanosheets comprises molybdenum sulfide and metal cation-doped cobalt sulfide;

[0007] The metal cations include nickel ions and / or manganese ions.

[0008] Preferably, the thickness of the polymetallic sulfide nanosheet is 5 to 30 nm; the particle size of the metal cation-doped polymetallic sulfide nanosphere is 500 nm to 2 μm, and the specific surface area is 0.01 to 5 m 2 / g, and the pore size distribution is 1 to 50 nm.

[0009] The present invention also provides a method for preparing the metal cation-doped polymetallic sulfide nanospheres described in the above technical solution, comprising the following steps:

[0010] Mixing a dispersion of a metal organic framework material, a molybdate and a sulfur-containing compound, and performing a hydrothermal reaction or a solvothermal reaction to obtain the metal cation-doped polymetallic sulfide nanospheres;

[0011] The metal cations in the metal organic framework material include cobalt ions and nickel ions, or cobalt ions and manganese ions, or cobalt ions, nickel ions and manganese ions.

[0012] Preferably, the organic ligand in the metal organic framework material comprises 2-methylimidazole and / or terephthalic acid.

[0013] Preferably, the sulfur-containing compound includes one or more of thiourea, thioacetamide, ammonium sulfide and sodium thiosulfate.

[0014] Preferably, the temperature of the hydrothermal reaction or the solvothermal reaction is 180-220° C., and the insulation time is 6-24 hours.

[0015] Preferably, the molybdate is sodium molybdate.

[0016] Preferably, after the hydrothermal reaction or the solvothermal reaction, the process further comprises: cooling the product obtained from the hydrothermal reaction or the solvothermal reaction to room temperature, separating the solid from the liquid, and sequentially washing and drying the obtained solid; the drying temperature is 60 to 120° C.; and the drying time is 6 to 12 hours.

[0017] The present invention also provides the use of the metal cation doped polymetallic sulfide nanospheres described in the above technical solution or the metal cation doped polymetallic sulfide nanospheres prepared by the preparation method described in the above technical solution as catalysts in electrolysis of water.

[0018] The present invention also provides a method for electrolyzing water, comprising the following steps:

[0019] A two-electrode system is used in an electrochemical workstation to electrolyze water to produce hydrogen and oxygen;

[0020] The cathode and anode of the two-electrode system are both nickel foam coated with metal cation-doped polymetallic sulfide nanospheres;

[0021] The metal cation doped polymetallic sulfide nanospheres are the metal cation doped polymetallic sulfide nanospheres described in the above technical solution or the metal cation doped polymetallic sulfide nanospheres prepared by the preparation method described in the above technical solution.

[0022] The present invention provides a metal cation doped multimetal sulfide nanosphere, which is formed by multimetal sulfide nanosheets, wherein the multimetal sulfide in the multimetal sulfide nanosheets includes molybdenum sulfide and metal cation doped cobalt sulfide; the metal cation includes nickel ions and / or manganese ions. The material is a nanosphere formed by cross-linking multimetal sulfide nanosheets, the nanosheets are cross-linked to form a network, the specific surface area is large, more active sites can be exposed, the transfer and transmission of charges are promoted, and the diffusion and separation of bubbles in the hydrogen and oxygen evolution reactions are promoted, the hydrogen and oxygen evolution reactions are accelerated, and the bifunctional catalytic activity of the hydrogen and oxygen evolution reactions is improved. The metal cation doping changes the electronic structure of cobalt sulfide through the defects produced by the metal cation doping, and its catalytic activity can be improved. The metal cation doped multimetal sulfide nanospheres can have excellent bifunctional catalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) by compounding with molybdenum sulfide, and show excellent water electrolysis performance, which can effectively improve the catalytic efficiency of water electrolysis.

[0023] The present invention also provides a method for preparing the metal cation-doped polymetallic sulfide nanospheres. The present invention generates a metal organic framework material with cobalt and metal cations (nickel or manganese) coordination through a coordination reaction, and then generates molybdenum sulfide and cobalt sulfide by subjecting the metal organic framework material to a hydrothermal reaction or a solvothermal reaction with molybdate and a sulfur-containing compound, and cobalt sulfide is doped with nickel ions or manganese ions, and polymetallic sulfide nanosheets are formed into nanospheres. Moreover, the preparation method is simple, low-cost, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of a three-electrode system and a two-electrode system;

[0025] Figure 2 LSV curves of HER (a) and OER (b) of Co-Ni-Mo-S prepared in Example 1, Co-Mn-Mo-S prepared in Example 2, Co-Mo-S prepared in Comparative Example 1, and Mo-S prepared in Comparative Example 2;

[0026] Figure 3 The LSV curve of the Co-Ni-Mo-S prepared in Example 1 as a catalyst for electrolysis of water (a) and the it curve of the Co-Ni-Mo-S prepared in Example 1 (b);

[0027] Figure 4XRD patterns of Co-Ni-Mo-S prepared in Example 1 and Co-Mo-S prepared in Comparative Example 1;

[0028] Figure 5 The SEM images and mapping images of the Co-ZIF prepared in Comparative Example 1 and the Co-Ni-ZIF prepared in Example 1;

[0029] Figure 6 SEM images and mapping images of Co-Ni-Mo-S prepared in Example 1 at different magnifications. DETAILED DESCRIPTION

[0030] The present invention provides a metal cation-doped polymetallic sulfide nanosphere, wherein the nanosphere is formed from polymetallic sulfide nanosheets, wherein the polymetallic sulfide in the polymetallic sulfide nanosheets comprises molybdenum sulfide and metal cation-doped cobalt sulfide;

[0031] The metal cations include nickel ions and / or manganese ions.

[0032] In the present invention, the metal cations include nickel ions and / or manganese ions, more preferably nickel ions.

[0033] In the present invention, the thickness of the polymetallic sulfide nanosheet is preferably 5 to 30 nm, more preferably 8 to 12 nm; the particle size of the metal cation-doped polymetallic sulfide nanosphere is preferably 500 nm to 2 μm, more preferably 500 nm to 1 μm or 1.3 to 1.8 μm, and the specific surface area is preferably 0.01 to 5 m 2 / g, more preferably 2 to 5 m 2 / g, most preferably 2.7m 2 / g or 4.3m 2 / g, and the pore size distribution is preferably 1 to 50 nm, more preferably 2 to 16 nm or 2 to 22 nm.

[0034] In the nanospheres formed by cross-linking of multi-metal sulfide nanosheets, the nanosheets are cross-linked to form a network with a large specific surface area, which can expose more active sites, promote the transfer and transmission of charges, and promote the diffusion and detachment of bubbles during hydrogen evolution and oxygen evolution reactions, accelerate the hydrogen evolution and oxygen evolution reactions, and improve the bifunctional catalytic activity of hydrogen evolution and oxygen evolution reactions. Metal cation doping can improve its catalytic activity by changing the electronic structure of cobalt sulfide through the defects it creates. Composite with molybdenum sulfide can make the metal cation-doped multi-metal sulfide nanospheres have excellent bifunctional catalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), showing excellent water electrolysis performance, which can effectively improve the catalytic efficiency of water electrolysis.

[0035] The present invention also provides a method for preparing the metal cation-doped polymetallic sulfide nanospheres described in the above technical solution, comprising the following steps:

[0036] Mixing a dispersion of a metal organic framework material, a molybdate and a sulfur-containing compound, and performing a hydrothermal reaction or a solvothermal reaction to obtain the metal cation-doped polymetallic sulfide nanospheres;

[0037] The metal cations in the metal organic framework material include cobalt ions and nickel ions, or cobalt ions and manganese ions, or cobalt ions, nickel ions and manganese ions.

[0038] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.

[0039] The invention mixes a dispersion of a metal organic framework material, molybdate and a sulfur-containing compound, and performs a hydrothermal reaction or a solvent thermal reaction to obtain the metal cation-doped polymetallic sulfide nanospheres.

[0040] In the present invention, the metal cations in the metal organic framework material include cobalt ions and nickel ions, or cobalt ions and manganese ions, or cobalt ions, nickel ions and manganese ions, preferably cobalt ions and nickel ions.

[0041] In the present invention, the preparation method of the metal organic framework material preferably includes the following steps: mixing a solution of a metal salt and a solution of an organic ligand to carry out a coordination reaction to obtain a metal organic framework material; the metal salt preferably includes a cobalt salt and a nickel salt, or a cobalt salt and a manganese salt, or a cobalt salt, a nickel salt and a manganese salt, more preferably a cobalt salt and a nickel salt; the cobalt salt preferably includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate, more preferably cobalt nitrate; the nickel salt preferably includes one or more of nickel sulfate, nickel nitrate and nickel chloride, more preferably nickel sulfate; the manganese salt preferably includes one or more of manganese chloride, manganese sulfate and manganese nitrate, more preferably manganese chloride; the organic ligand includes 2-methylimidazole and / or terephthalic acid, more preferably 2-methylimidazole.

[0042] In the present invention, the molar ratio of the metal salt to the organic ligand is preferably 1:1-10, more preferably 1:4; the molar ratio of the cobalt salt to the nickel salt is preferably 1-4:1-4, more preferably 4:1; the molar ratio of the cobalt salt to the manganese salt is preferably 1-4:1-4, more preferably 4:1.

[0043] In the present invention, the method for preparing the solution of the metal salt is preferably to mix the metal salt and the first solvent and stir or ultrasonicate; the first solvent preferably includes one or more of methanol, ethanol, water, N,N-dimethylformamide and N,N-dimethylacetamide, more preferably methanol; the ultrasonication time is preferably 10 to 60 minutes, more preferably 30 minutes. The present invention has no special limitation on the amount of the first solvent, and the amount of solvent well known in the art can be used.

[0044] In the present invention, the method for preparing the solution of the organic ligand is preferably to mix the organic ligand and the second solvent and stir or ultrasonicate; the second solvent preferably includes one or more of methanol, ethanol, water, N,N-dimethylformamide and N,N-dimethylacetamide, more preferably methanol; the ultrasonication time is preferably 10 to 60 minutes, more preferably 30 minutes. The present invention has no special limitation on the amount of the second solvent, and the amount of solvent well known in the art can be used.

[0045] In the present invention, the coordination reaction is preferably stirred first and then allowed to stand at room temperature; the room temperature is preferably 20-30°C, more preferably 25°C; the stirring rate is preferably 800-2000rpm, more preferably 1000-1500rpm, and the time is preferably 5-30min, more preferably 10-20min; the standing time is preferably 6-24h, more preferably 12-20h.

[0046] During the coordination reaction, metal salts (cobalt salts and nickel salts, or cobalt salts and manganese salts, or cobalt salts, nickel salts and manganese salts) are coordinated with organic ligands to generate metal-organic framework materials.

[0047] After the coordination reaction, the present invention preferably further comprises: separating the solid-liquid of the system obtained by the coordination reaction, and washing and drying the obtained solid in sequence to obtain a metal organic framework material. In the present invention, the washing preferably comprises water washing and / or alcohol washing; the water used for the water washing is preferably deionized water; the alcohol used for the alcohol washing is preferably anhydrous ethanol; the number of washings is preferably 2 to 5 times, more preferably 3 to 5 times, and most preferably 4 times; the drying temperature is preferably 60 to 120°C, more preferably 60 to 100°C, and most preferably 80°C; the drying time is preferably 6 to 12h, more preferably 8 to 10h; the equipment used for drying is preferably an electric constant temperature blast drying oven. The present invention does not specifically limit the method of solid-liquid separation, and the solid-liquid separation method well known in the art can be used. In an embodiment of the present invention, the solid-liquid separation is preferably centrifugation.

[0048] In the present invention, the method for preparing the dispersion of the metal organic framework material is preferably to mix the metal organic framework material and a third solvent and perform ultrasonic treatment; the third solvent is preferably deionized water; the amount ratio of the metal organic framework material and the third solvent is preferably (10-50) mg: (30-80) mL, more preferably (20-30) mg: (50-60) mL; the time of the ultrasonic treatment is preferably 10-60 min, more preferably 30-40 min. The present invention has no special restrictions on the power and frequency of the ultrasonic treatment, as long as the metal organic framework material can be evenly dispersed.

[0049] In the present invention, the molybdate is preferably sodium molybdate; the sulfur-containing compound preferably includes one or more of thiourea, thioacetamide, ammonium sulfide and sodium thiosulfate, and is more preferably thiourea; the molar ratio of the molybdate to the sulfur-containing compound is preferably 1:2-10, more preferably 1:4-6, and most preferably 1:5; the molar ratio of the metal organic framework material to the sulfur-containing compound is preferably 1:20-100, more preferably 1:40-60, and most preferably 1:50.

[0050] In the present invention, the temperature of the hydrothermal reaction or the solvothermal reaction is preferably 180 to 220° C., more preferably 190 to 200° C., and the insulation time is preferably 6 to 24 h, more preferably 12 to 18 h.

[0051] In the hydrothermal reaction, the metal organic framework material will be etched by the sulfur-containing compound, gradually and slowly releasing the metal ions, and it is not easy to agglomerate, so the effect of doping and sulfurization is better than directly adding metal salts. Molybdate reacts with sulfur-containing compounds to form molybdenum sulfide, and the metal organic framework material reacts with sulfur-containing compounds to form cobalt sulfide doped with metal cations (nickel ions or manganese ions). Doping will cause the cobalt sulfide lattice distortion, thereby generating a large number of defects and improving the catalytic activity.

[0052] After the hydrothermal reaction or the solvothermal reaction, the present invention preferably further comprises: cooling the product obtained from the hydrothermal reaction or the solvothermal reaction to room temperature, separating the solid from the liquid, and sequentially washing and drying the obtained solid; the cooling is preferably natural cooling; the washing is preferably water washing; the drying temperature is 60 to 120°C, more preferably 80 to 100°C; the drying time is 6 to 12h, more preferably 8 to 12h; the drying equipment used is preferably an electric constant temperature blast drying oven.

[0053] The present invention also provides the use of the metal cation doped polymetallic sulfide nanospheres described in the above technical solution or the metal cation doped polymetallic sulfide nanospheres prepared by the preparation method described in the above technical solution as catalysts in electrolysis of water.

[0054] The present invention has no special limitation on the application of the metal cation-doped polymetallic sulfide nanospheres as catalysts in water electrolysis, and any application method known in the art may be used.

[0055] The present invention also provides a method for electrolyzing water, comprising the following steps:

[0056] A two-electrode system is used in an electrochemical workstation to electrolyze water to produce hydrogen and oxygen;

[0057] The cathode and anode of the two-electrode system are both nickel foam coated with metal cation-doped polymetallic sulfide nanospheres;

[0058] The metal cation doped polymetallic sulfide nanospheres are the metal cation doped polymetallic sulfide nanospheres described in the above technical solution or the metal cation doped polymetallic sulfide nanospheres prepared by the preparation method described in the above technical solution.

[0059] In the present invention, the method for preparing the nickel foam coated with metal cation-doped polymetallic sulfide nanospheres is preferably: mixing the metal cation-doped polymetallic sulfide nanospheres, a binder and alcohol, coating the resulting mixed slurry on the nickel foam, and drying. In the present invention, the binder is preferably a nafion solution with a mass concentration of 5%; the mass ratio of the metal cation-doped polymetallic sulfide nanospheres to the binder is preferably 1-4:1-4, more preferably 1-2:1-2; the amount ratio of the metal cation-doped polymetallic sulfide nanospheres to alcohol is preferably 4 mg:0.2 mL; the area of ​​the nickel foam coated with the metal cation-doped polymetallic sulfide nanospheres is preferably 0.5 cm×0.5 cm; the voltage window of the two-electrode system is preferably 0-2 V, and the scan rate is preferably 5 mV·s -1 ; The electrolyte of the two-electrode system is preferably a KOH solution; the concentration of the KOH solution is preferably 1 mol / L; the electrochemical workstation is preferably a CHI-760E electrochemical workstation.

[0060] The present invention preferably further comprises: using a three-electrode system in an electrochemical workstation to perform a hydrogen evolution test and an oxygen evolution test; the working electrode of the three-electrode system is a nickel foam coated with metal cation-doped polymetallic sulfide nanospheres; the area of ​​the nickel foam coated with the metal cation-doped polymetallic sulfide nanospheres is preferably 0.5 cm×0.5 cm; the electrochemical workstation is preferably a CHI-760E electrochemical workstation; the reference electrode of the three-electrode system is preferably Hg / HgO, the counter electrode is preferably a carbon rod, and the electrolyte is preferably a KOH solution; the concentration of the KOH solution is preferably 1 mol / L; the voltage window of the hydrogen evolution test is preferably -1.5 to -0.7 V, and the scan rate is preferably 5 mV·s -1The voltage window of the oxygen evolution test is preferably 0-1V, and the scan rate is preferably 5mV·s -1 ; The present invention preferably converts the potential into a reversible hydrogen electrode (RHE) by adding (0.098+0.0591*pH)V.

[0061] Figure 1 Schematic diagram of a three-electrode system and a two-electrode system.

[0062] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0063] Example 1

[0064] 0.008 mol Co(NO3)2·6H2O and 0.002 mol nickel sulfate were ultrasonically treated in 80 mL CH3OH solution for 30 min to obtain a metal salt solution. 3.284 g 2-methylimidazole (0.04 mol) was ultrasonically treated in 80 mL CH3OH solution for 30 min to obtain a 2-methylimidazole solution. The molar ratio of the metal salt to 2-methylimidazole was 1:4. The 2-methylimidazole solution was slowly poured into the metal salt solution. After stirring at 1000 rpm for 10 min at 25°C, the mixture was allowed to stand for 12 h for coordination reaction. The obtained product was centrifuged and washed with CH3OH solution for 3 times to obtain a purple precipitate, which was then placed in a vacuum drying oven at 80°C and dried for 12 h. The obtained purple powder was named Co-Ni-ZIF.

[0065] 25 mg of Co-Ni-ZIF powder was weighed and placed in a clean beaker, 60 mL of deionized water was added, and ultrasonic treatment was performed for 30 min to obtain a Co-Ni-ZIF dispersion. 0.145 g of sodium molybdate and 0.426 g of thiourea were added in sequence, and ultrasonic treatment was continued for 30 min. The resulting mixture was transferred to a 100 mL high-pressure reactor, heated to 200 ° C in an electric blast drying oven and kept warm for 12 h for hydrothermal reaction. After the drying oven was naturally cooled to room temperature, the sample was taken out, and the solid-liquid separation was performed. After the obtained solid was washed with water, it was dried at 80 ° C in an electric constant temperature blast drying oven for 12 h to obtain metal cation-doped multimetallic sulfide nanospheres, named Co-Ni-Mo-S (size 500 nm~1 μm, specific surface area 4.3 m 2 / g, pore size distribution is 2 to 22 nm).

[0066] Example 2

[0067] The difference from Example 1 is that the nickel sulfate in Example 1 is replaced by the same mole of manganese chloride to obtain Co-Mn-ZIF, and then the Co-Ni-ZIF in Example 1 is replaced by Co-Mn-ZIF to prepare Co-Mn-Mo-S (with a particle size of 1.3 to 1.8 μm and a specific surface area of ​​2.7 m 2 / g, pore size distribution is 2 to 16 nm).

[0068] Comparative Example 1

[0069] 2.910 g of Co(NO3)2·6H2O (0.01 mol) and 3.284 g of 2-methylimidazole (0.04 mol) were ultrasonically treated in 80 mL of CH3OH solution at a molar ratio of 1:4 for 30 min, and the 2-methylimidazole solution was slowly poured into the cobalt nitrate solution. After stirring at 1000 rpm for 10 min at 25°C, the solution was allowed to stand for 12 h for coordination reaction. The product was centrifuged and washed with CH3OH solution 5 times. The purple precipitate was placed in a vacuum drying oven at 80°C and dried for 12 h. The purple powder obtained was named ZIF-67.

[0070] Co-Mo-S was prepared by replacing the Co-Ni-ZIF in Example 1 with ZIF-67.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that the Co-Ni-ZIF powder is removed, and molybdenum sulfide is directly prepared by hydrothermal reaction of sodium molybdate and thiourea, which is named Mo-S.

[0073] Application Example 1

[0074] A two-electrode system was used to electrolyze water in a CHI-760E electrochemical workstation to produce hydrogen and oxygen.

[0075] The cathode and anode of the two-electrode system are both nickel foam coated with metal cation-doped multimetal sulfide nanospheres prepared in Example 1;

[0076] The preparation method of the nickel foam coated with the metal cation-doped polymetallic sulfide nanospheres prepared in Example 1 is as follows: the metal cation-doped polymetallic sulfide nanospheres, an adhesive and alcohol are mixed, the obtained mixed slurry is coated on the nickel foam, and then dried; the adhesive is a nafion solution with a mass concentration of 5%; the mass ratio of the metal cation-doped polymetallic sulfide nanospheres to the adhesive is 2:1; the amount ratio of the metal cation-doped polymetallic sulfide nanospheres to the alcohol is 4 mg:0.2 mL; the area of ​​the nickel foam coated with the metal cation-doped polymetallic sulfide nanospheres is 0.5 cm×0.5 cm; the voltage window of the two-electrode system is 0-2 V, and the scanning rate is 5 mV·s -1 ; The electrolyte of the two-electrode system is KOH solution; The concentration of the KOH solution is 1 mol / L.

[0077] Performance Testing

[0078] Figure 2 LSV curves of HER (a) and OER (b) of Co-Ni-Mo-S prepared in Example 1, Co-Mn-Mo-S prepared in Example 2, Co-Mo-S prepared in Comparative Example 1, and Mo-S prepared in Comparative Example 2. The specific test method is as follows: a three-electrode system is used in an electrochemical workstation to perform a hydrogen evolution test and an oxygen evolution test; the working electrodes of the three-electrode system are nickel foams coated with Co-Ni-Mo-S prepared in Example 1, Co-Mn-Mo-S prepared in Example 2, Co-Mo-S prepared in Comparative Example 1, and Mo-S prepared in Comparative Example 2, respectively; the coating area on the nickel foam is 0.5 cm×0.5 cm; the electrochemical workstation is a CHI-760E electrochemical workstation; the reference electrode of the three-electrode system is Hg / HgO, the counter electrode is a carbon rod, and the electrolyte is a KOH solution; the concentration of the KOH solution is 1 mol / L; the voltage window of the hydrogen evolution test is -1.5 to -0.7 V, and the scan rate is preferably 5 mV·s -1 The voltage window of the oxygen evolution test is 0-1V, and the scan rate is preferably 5mV·s -1 ; By adding (0.098+0.0591*pH)V, the potential was converted to reversible hydrogen electrode (RHE) for easy comparison.

[0079] from Figure 2 It can be seen that when the same current density is achieved, the overpotential required for Co-Ni-Mo-S is the smallest, indicating that Co-Ni-Mo-S has better catalytic performance in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).

[0080] Figure 3The LSV curve (a) and IT curve (b) of the Co-Ni-Mo-S prepared in Example 1 as a catalyst for electrolysis of water. Figure 3 As can be seen, reaching 10mA·cm -2 When the current density is 1.55V, the overpotential required for Co-Ni-Mo-S is 1.55V, indicating that Co-Ni-Mo-S has good catalytic performance for water electrolysis. After 15h, the current density of Co-Ni-Mo-S prepared in Example 1 still remains at 95.6% of the initial value, indicating that it has good stability and has the potential to become a high catalytic performance water electrolysis catalyst.

[0081] Figure 4 The XRD diagrams of Co-Ni-Mo-S prepared in Example 1 and Co-Mo-S prepared in Comparative Example 1 are shown in the figure, where the inset is a partial enlarged view. Figure 4 It can be seen that the crystal phases of Co-Mo-S correspond to MoS2 (37-1692) and CoS2 (41-1471), respectively, indicating that MoS2 and CoS2 are generated after Co-ZIF is sulfided. During the hydrothermal process, sodium molybdate reacts with thiourea to generate MoS2, and Co-ZIF reacts with thiourea to generate CoS2. In addition, thiourea etches Co-Ni-ZIF to release cobalt ions and nickel ions, causing the 44.8° peak of Co-Ni-Mo-S to shift positively compared with the peak of Co-Mo-S (44.5°) (enlarged inset). The doping or substitution of Ni ions leads to the distortion of the CoS2 lattice. Since the radius of the doped Ni atom is smaller than that of the Co atom, the interlayer distance of CoS2 is reduced. In summary, Co-Ni-ZIF is sulfided to generate MoS2 and Ni-doped CoS2.

[0082] Figure 5 The SEM images and mapping images of Co-ZIF prepared in Comparative Example 1 and Co-Ni-ZIF prepared in Example 1, where (a) and (b) are Co-ZIF, (c) and (d) are Co-Ni-ZIF. Figure 5 It can be seen that Co-ZIF and Co-Ni-ZIF have typical rhombic dodecahedron morphology with a particle size of 500nm to 1μm. In the mapping diagrams of Co-ZIF and Co-Ni-ZIF in Figures (b) and (d), it can be seen that compared with Co-ZIF, the rhombic dodecahedron structure of Co-Ni-ZIF is not affected by Ni 2+ was destroyed by the addition of , indicating that Co-Ni-ZIF was successfully prepared.

[0083] Figure 6The SEM images and mapping images of Co-Ni-Mo-S prepared in Example 1 at different magnifications, where (a) is at a magnification of 7K, (b) is at a magnification of 150K, and (c) is at a magnification of 70K and the corresponding element distribution map, i.e., mapping. Figure 6 It can be seen that the morphology of Co-Ni-Mo-S is a nanosphere of cross-stacked nanosheets, the thickness of the nanosheets is about 10nm, and the size of the nanospheres is 500nm~1μm. The nanosheets have a large specific surface area, which is conducive to exposing more active sites. In addition, this special structure is also conducive to the diffusion and escape of bubbles. From the mapping diagram of Co-Ni-Mo-S, it can be seen that the Co-Ni-Mo-S sample contains Co, Ni, Mo and S elements, indicating that Co-Ni-ZIF forms Co-Ni-Mo-polymetallic sulfide nanospheres after sulfidation.

[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A metal cation doped polymetallic sulfide nanosphere, characterized in that: Forming nanospheres from polymetallic sulfide nanosheets, wherein the polymetallic sulfide in the polymetallic sulfide nanosheets includes molybdenum sulfide and metal cation-doped cobalt sulfide; The metal cations include nickel ions and / or manganese ions.

2. The metal cation doped polymetallic sulfide nanospheres according to claim 1, characterized in that: The thickness of the polymetallic sulfide nanosheet is 5 to 30 nm; the particle size of the metal cation-doped polymetallic sulfide nanosphere is 500 nm to 2 μm, and the specific surface area is 0.01 to 5 m 2 / g, and the pore size distribution is 1 to 50 nm.

3. The method for preparing metal cation-doped polymetallic sulfide nanospheres according to claim 1 or 2, characterized in that: The following steps are involved: Mixing a dispersion of a metal organic framework material, a molybdate and a sulfur-containing compound, and performing a hydrothermal reaction or a solvothermal reaction to obtain the metal cation-doped polymetallic sulfide nanospheres; The metal cations in the metal organic framework material include cobalt ions and nickel ions, or cobalt ions and manganese ions, or cobalt ions, nickel ions and manganese ions.

4. The preparation method according to claim 3, characterized in that: The organic ligands in the metal organic framework material include 2-methylimidazole and / or terephthalic acid.

5. The preparation method according to claim 3, characterized in that: The sulfur-containing compound includes one or more of thiourea, thioacetamide, ammonium sulfide and sodium thiosulfate.

6. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction or solvent thermal reaction is 180-220° C., and the insulation time is 6-24 hours.

7. The preparation method according to claim 3, characterized in that: The molybdate is sodium molybdate.

8. The preparation method according to claim 3, characterized in that: After the hydrothermal reaction or the solvothermal reaction, the method further comprises: cooling the product obtained from the hydrothermal reaction or the solvothermal reaction to room temperature, separating the solid from the liquid, and washing and drying the obtained solid in sequence; the drying temperature is 60 to 120° C.; and the drying time is 6 to 12 hours.

9. Use of the metal cation-doped polymetallic sulfide nanospheres according to claim 1 or 2 or the metal cation-doped polymetallic sulfide nanospheres prepared by the preparation method according to any one of claims 3 to 8 as a catalyst in electrolysis of water.

10. A method for electrolyzing water, characterized in that: The following steps are involved: A two-electrode system is used in an electrochemical workstation to electrolyze water to produce hydrogen and oxygen; The cathode and anode of the two-electrode system are both nickel foam coated with metal cation-doped polymetallic sulfide nanospheres; The metal cation doped polymetallic sulfide nanospheres are the metal cation doped polymetallic sulfide nanospheres according to claim 1 or 2 or the metal cation doped polymetallic sulfide nanospheres prepared by the preparation method according to any one of claims 3 to 8.

Citation Information

Cited By

  • Iron-based multi-metal sulfide composite carbon anode material and preparation method thereof

    CN121484083A